Human β-D-3 Exacerbates MDA5 but Suppresses TLR3 Responses to the Viral Molecular Pattern Mimic Polyinosinic:Polycytidylic Acid - Semple, Fiona (PLoS Genet, 2015)
Human β-defensin 3 (hBD3) is a cationic host defence peptide and is part of the innate immune response. HBD3 is present on a highly copy number variable block of six β-defensin genes, and increased copy number is associated with the autoimmune disease psoriasis. It is not known how this increase influences disease development, but psoriasis is a T cell-mediated disease and activation of the innate immune system is required for the initial trigger that leads to the amplification stage. We investigated the effect of hBD3 on the response of primary macrophages to various TLR agonists. HBD3 exacerbated the production of type I Interferon-β in response to the viral ligand mimic polyinosinic:polycytidylic acid (polyI:C) in both human and mouse primary cells, although production of the chemokine CXCL10 was suppressed. Compared to polyI:C alone, mice injected with both hBD3 peptide and polyI:C also showed an enhanced increase in Interferon-β. Mice expressing a transgene encoding hBD3 had elevated basal levels of Interferon-β, and challenge with polyI:C further increased this response. HBD3 peptide increased uptake of polyI:C by macrophages, however the cellular response and localisation of polyI:C in cells treated contemporaneously with hBD3 or cationic liposome differed. Immunohistochemistry showed that hBD3 and polyI:C do not co-localise, but in the presence of hBD3 less polyI:C localises to the early endosome. Using bone marrow derived macrophages from knockout mice we demonstrate that hBD3 suppresses the polyI:C-induced TLR3 response mediated by TICAM1 (TRIF), while exacerbating the cytoplasmic response through MDA5 (IFIH1) and MAVS (IPS1/CARDIF). Thus, hBD3, a highly copy number variable gene in human, influences cellular responses to the viral mimic polyI:C implying that copy number may have a significant phenotypic effect on the response to viral infection and development of autoimmunity in humans.